PEMBUATAN DAN UJI STABILITAS SEDIAAN SERBUK INSTAN DAUN GEDI HIJAU (Abelmoschus manihot L.) UNTUK MENINGKATKAN KESEHATAN TUBUH - Isfina Azmiyanti; Jenta Puspariki; Risa Kota Putra (Sekolah Tinggi Ilmu Kesehatan Holistik, 2022)
Background: Since long ago Indonesian people often use medicinal plants, one of which is the community of Kel. Ciseureuh Purwakarta who use gedi leaves (Abelmoschus manihot L.) to reduce fever, defecate and relieve deep heat. Gedi leaves have a pharmacological effect as an antioxidant, where the pharmacological effect of these antioxidants comes from flafonoid content. Purpose: This study aims to find out how to make instant powder preparations, the stability of instant powder preparations based on organoleptic tests and the level of public fondness for gedi leaf instant powder preparations. Method: The research method used is to use action research methods consisting of four components, namely planning, action, observation, and reflection. Instant powder preparations are made with 500 grams of wet gedi leaves, then made into 1500 ml of liquid extract, then divided into three formulas that each 500 ml of F1 liquid extract with white crystal sugar 2, F2 with white crystal sugar 1, and F3 with palm sugar as much as 250 gr. Conclusion: The conclusion of this study is the most stable instant powder preparation for three weeks and most preferred by respondents, namely F1 white crystal sugar 2.